2022
DOI: 10.1080/21655979.2021.2009414
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA 0000654 facilitates the growth of gastric cancer cells through absorbing microRNA-149-5p to up-regulate inhibin-beta A

Abstract: Circular (circ) RNAs are differentially expressed in gastric cancer (GC) and participate in the biological growth of tumor cells. Given that, investigations were performed to unravel the function of circ_0000654 in GC. GC tissue and normal tissue specimens were obtained, in which circ_0000654, microRNA (miR)-149-5p, and inhibin-beta A (INHBA) levels were examined. GC cell line (BGC-823) was transfected to alter circ_0000654 and miR-149-5p expression, thereby observing cell malignancy. Stably-transfected BGC-82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Circ_0005320 facilitates oral squamous cell carcinoma tumorigenesis via sponging miRNA-486-3p and miRNA-637 [ 9 ]. Circ_0000654 that absorbs miRNA-149-5p to upregulate inhibin-beta A enhances the growth of gastric cancer cells [ 10 ]. Moreover, Zheng Q et al [ 11 ] has discovered that circHIPK3 is the most abundant among the three distinct types of splicing bodies in the circRNAs of the HIPK3 gene, which plays a critical role in cells growth through sponging multiple miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Circ_0005320 facilitates oral squamous cell carcinoma tumorigenesis via sponging miRNA-486-3p and miRNA-637 [ 9 ]. Circ_0000654 that absorbs miRNA-149-5p to upregulate inhibin-beta A enhances the growth of gastric cancer cells [ 10 ]. Moreover, Zheng Q et al [ 11 ] has discovered that circHIPK3 is the most abundant among the three distinct types of splicing bodies in the circRNAs of the HIPK3 gene, which plays a critical role in cells growth through sponging multiple miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that abnormal expression of INHBA exerted various biological functions in different tumor development processes. For instance, the inhibitory role of INHBA in the growth of lung cancer and head and neck squamous cell carcinoma is not obvious, but it enhances the invasive ability of tumor cells, which involves many processes of the body and embryonic development, including cell growth, differentiation, apoptosis, homeostasis and so on [ 4 ]. The expression level of INHBA in various malignant tumor tissues, such as gastric cancer and breast cancer, is significantly increased.…”
Section: Introductionmentioning
confidence: 99%